The influence of particle size of Engen Feed corn and conventional yellow dent corn on nursery and finishing pig performance, carcass characteristics and stomach morphology - Williams, Hadley (Kansas State University, 2020)
Enogen Feed corn is a corn hybrid developed by Syngenta Seeds that has been genetically modified to contain an α-amylase enzyme trait (SYT-EFC). Several approaches to compare Enogen Feed corn and conventional yellow dent corn were evaluated including interventions within the feed manufacturing process to maximize animal performance. A total of 2,513 pigs were used in a total of 4 experiments structured in 3 chapters. Chapter 1 evaluated the influence of particle size and Enogen Feed corn and conventional yellow dent corn on nursery and finishing pig performance, carcass characteristics and stomach morphology. The six experimental treatments included Enogen Feed corn and conventional yellow dent corn ground to 3 different particle sizes: 300, 600, and 900 microns. For nursery pigs there was a corn source × particle size interaction for gain to feed (G:F) ratio. There was no difference due to particle size when pigs were fed conventional yellow dent corn, but in pigs fed Enogen Feed corn, G:F decreased with increasing particle size. Neither corn source nor particle size affected average daily gain (ADG) or average daily feed intake (ADFI). For finishing pigs, there were no differences observed among pigs fed either corn source for ADG, ADFI or G:F while G:F increased linearly as corn particle size decreased. Chapter 2 evaluated the influence of particle size of Enogen Feed corn and conventional yellow dent corn on lactating sow and their offspring performance. We observed no differences when comparing Enogen Feed corn and conventional yellow dent corn on lactating sow and litter performance. Litter ADG and overall litter gain tended to be greater in sows fed 600-micron corn compared to sows fed diets with 900 microns. Chapter 3 evaluated the influence of Enogen Feed corn and conventional yellow dent corn in pelleted- or meal- based diets on finishing pig performance and carcass characteristics. Feeding pelleted diets to pigs increased ADG and improved G:F with no major differences between corn sources on growth performance.
Keywords: Corn variety; Growth performance; Particle size; Swine